2004
DOI: 10.1111/j.1479-8301.2004.00063.x
|View full text |Cite
|
Sign up to set email alerts
|

Dual inverse effects of lipoprotein(a) on the dementia process in Japanese late‐onset Alzheimer's disease

Abstract: Background: The role of lipoprotein metabolism in the dementia process has attracted increasing attention. It is universally accepted that apolipoprotein E4 (ApoE) is a risk factor for late-onset Alzheimer's disease, however, the role of lipoprotein(a) (Lp(a)) remains unclear. Therefore, we conducted the present study to clarify the association between Lp(a) and dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Abnormal metabolism of lipoproteins such as lipoprotein (a)/Lp(a) and their variants has been associated with peripheral artery disease, stroke, atherosclerosis, cerebrovascular disease as well as AD ( 146 , 147 ) . Coconut oil has been shown to help reduce Lp (a) levels, and the addition of coconut oil to the diet may improve cholesterol metabolism.…”
Section: Coconut Oil and Lipid Metabolismmentioning
confidence: 99%
“…Abnormal metabolism of lipoproteins such as lipoprotein (a)/Lp(a) and their variants has been associated with peripheral artery disease, stroke, atherosclerosis, cerebrovascular disease as well as AD ( 146 , 147 ) . Coconut oil has been shown to help reduce Lp (a) levels, and the addition of coconut oil to the diet may improve cholesterol metabolism.…”
Section: Coconut Oil and Lipid Metabolismmentioning
confidence: 99%
“…However, data on the association between Lp(a) and risk of dementia are sparse and inconsistent. Whereas some studies have shown higher levels of Lp(a) to be linked with increased dementia risk,(6) some have shown a protective effect, (6)(7)(8) and others have shown no association at all. (9) However, due to the case-control design of these previous studies, the temporal sequence of the relationship between Lp(a) and cognitive decline has not been established and whether elevated Lp(a) levels increase or decrease the risk of future dementia is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“… 38 Third, apolipoprotein(a), primary determiner of the plasma Lp(a) level, may modify ApoE isoform metabolism, which is a key player in lipid metabolism. 39 Previous study showed that APOE ε2 and APOE ε4 were associated with MRI markers of cSVD. 40 Nevertheless, more researches are warranted to further elucidate the mechanisms for the inverse associations between Lp(a) level and cSVD.…”
Section: Discussionmentioning
confidence: 96%
“…It is suspected that Lp(a) may contribute to lipoprotein metabolism in the brain and glioneurovascular unit maintenance 38. Third, apolipoprotein(a), primary determiner of the plasma Lp(a) level, may modify ApoE isoform metabolism, which is a key player in lipid metabolism 39. Previous study showed that APOE ε2 and APOE ε4 were associated with MRI markers of cSVD 40.…”
Section: Discussionmentioning
confidence: 99%